2013
DOI: 10.1097/brs.0b013e318261ec74
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Outcomes of Combined Anterior and Posterior Spinal Fusion for Dystrophic Thoracolumbar Spinal Deformities of Neurofibromatosis-1

Abstract: APSF with FSAG for dystrophic deformity in NF-1 successfully reconstructed a reliable spinal column with a rich bone stock. The FSAG and surrounding vertebral bodies were free from postoperative erosion due to dystrophic changes and maintained their stability for a long time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
18
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 13 publications
1
18
0
Order By: Relevance
“…There are studies that report good outcomes with the PVCR technique for the treatment of severe vertebral deformities in idiopathic, congenital, and neuromuscular deformities, 13 but the literature addressing deformities secondary to NF-1 corrected using the PVCR technique are very scarce. 6,19 In our study, we observed good results in relation to the rate of correction, consolidation, and associated complications.…”
Section: Discussionsupporting
confidence: 57%
“…There are studies that report good outcomes with the PVCR technique for the treatment of severe vertebral deformities in idiopathic, congenital, and neuromuscular deformities, 13 but the literature addressing deformities secondary to NF-1 corrected using the PVCR technique are very scarce. 6,19 In our study, we observed good results in relation to the rate of correction, consolidation, and associated complications.…”
Section: Discussionsupporting
confidence: 57%
“…The clinical and operative details from previous studies are shown in Table 6. Previous researchers recommended corpectomy and combined circumferential fusion to treat or correct dystrophic scoliosis in NF-1 patients 11,14,26) . Halmai et al 6) reported a series of 12 patients who underwent 3-week preoperative traction and then anterior release, posterior instrumentation and fusion were performed.…”
Section: Discussionmentioning
confidence: 99%
“…[58,11] The anterior strut-grafting from the concavity was recommended so that the graft undergoes compressive forces and conforms to biomechanical principle. [21] With anterior support of the spine and posterior instrumented fusion, the reconstructed spine could achieve stability and solid bony fusion would be generally seen at follow-up. The difficulty of this procedure lies in the high technique requirement of anterior approach and vulnerability of reconstructed anterior column because of poor local bone stock for placing a graft.…”
Section: Discussionmentioning
confidence: 99%